Open, High-Resolution EI+ Spectral Library of Anthropogenic Compounds - Elliott J. Price; Elliott J. Price; Jirí Palát; Katerina Coufaliková; Petr Kukučka; Garry Codling; Chiara Maria Vitale; Štěpán Koudelka; Jana Klánová (Frontiers Media S.A., 2021)
To address the lack of high-resolution electron ionisation mass spectral libraries (HR-[EI+]-MS) for environmental chemicals, a retention-indexed HR-[EI+]-MS library has been constructed following analysis of authentic compounds via GC-Orbitrap MS. The library is freely provided alongside a compound database of predicted physicochemical properties. Currently, the library contains over 350 compounds from 56 compound classes and includes a range of legacy and emerging contaminants. The RECETOX Exposome HR-[EI+]-MS library expands the number of freely available resources for use in full-scan chemical exposure studies and is available at: https://doi.org/10.5281/zenodo.4471217.